Factors affecting ICT usage for the development of small and medium agro-based enterprises in Selangor, Malaysia - Mohammed, Ibrahim Adamkolo (2017)
Information and communication technology (ICT) has been identified as a mean that has great potential to spur innovative development in small and medium-scale enterprises (SME). This study adopted the Unified Theory of Acceptance and Use of Technology (UTAUT) model perspective to investigate factors affecting ICT usage by agro-based SMEs in Selangor. This study aimed to achieve four specific objectives as follows: to identify the ICTs predominantly used by the agro-based SMEs in their businesses; to determine the factors that affect ICT usage among the agro-based SMEs; to determine the relationship between performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC), SME organisational size (SOS) and managerial creativity and innovativeness (MC&I) and ICT usage (IU); and to determine the moderating effect of gender, age and experience on the relationship between PE, EE, SI, FC, SOS and MC&I and IU. The UTAUT Model was adopted with some modifications by integrating two externally derived constructs, SME managerial creativity and SME organisational size as predictors. Furthermore, the behavioural intention dimension, which is also theorized to predict direct ICT usage, was dropped because many past studies have supported the claim that when a behavior becomes routine, it translates to habit, which is tantamount to automaticity. The moderation influence of only gender, age and experience was investigated as voluntariness of use was also dropped for convenience reasons. A questionnaire containing 132 items was administered to 400 workers (including managers). The workers were selected using purposive sampling from 43 agro-based SMEs in Selangor.After data collection, 395 completed questionnaires were retrieved successfully. The data was analysed using Statistical Package for Social Sciences (SPSS) version 22 and Structural Equation Model -Analysis of Moment Structure (SEM-AMOS) statistical software. The descriptive data and multiple regression analyses were performed using SPSS while factor analysis was performed using SEM-AMOS. SEM-AMOS was mainly used to test the hypotheses and determine the statistical fitness, or statistical strength of the new research model (also known as the structural model of this study), which was designed using SEM-AMOS to measure the research data adequately. To determine the statistical significance of each of the six predictors and their respective measurement items in the conceptual framework, principle component analysis (PCA) was ran. At PCA, social influence (SI) construct loaded with very weak items, which indicates that the construct was statistically non-significant, and if it was retained it would affect the statistical significance of the conceptual framework negatively, hence it was eliminated from the research framework as recommended in statistics rules. Thus, only five valid constructs remain in the conceptual framework of this study, namely performance expectancy, (PE), effort expectancy (EE), facilitating conditions (FC), managerial creativity and innovativeness (MC&I), SME organisational size (SOS) and ICT usage (IU). Furthermore, to confirm the statistical significance of each of the five remaining predictors with their respective measurement items, confirmatory factor analysis (CFA) was ran. CFA reduced the number of measurement items in each of the constructs to only three except for ICT usage construct, which was reduced to nine items. All the measurement items in the entire research scale recorded very high internal consistency reliability (Cronbach alpha) coefficient, ranging from 0.951 to 0.842, with a good overall model fit index (RMSEA) value = .79, indicating that the structural model was sufficiently fit to measure the data and yield valid results.The study found that performance expectancy, SME organisational size and SME managerial creativity and innovativeness significantly predicted ICT usage. In addition, age, gender and experience moderated the relationships at various levels of significance. Importantly however, performance expectancy was moderated by experience, which implies that agro-based SMEs that are run by employees and managers with prior ICT usage experience stand better chances of deriving much benefits from using ICT in their businesses. The structural (measurement) model predicted 31% (R2 0.31) of the variances associated with ICT usage. Therefore, the study concludes as follows. (1) That the anticipation of ICT usage benefits, enterprise organisational size and characteristics of enterprise managers, moderated by the workers' demographic characteristics and ICT usage experience are the critical factors that affect the usage of ICT by agro-based SMEs in Selangor; (2) gender, age and experience of the workers (as well as those of the managers) can influence ICT usage by agro-based SMEs in Selangor; and that (3) female employees using ICTs are more likely to perform work better and yield higher gains than their male counterparts may be able to do. Therefore, this study suggests that a paradigm shift from a maledominated industrial ICT usage bias towards a female-dominated one may be imminent, at least in Selangor context.